Penggunaan Model Pembelajaran Scramble dalam Meningkatkan Hasil Belajar IPS Siswa Kelas IV SDN 1 Penawar Jaya Tulang Bawang - Tiara, Shindy; Hidayat, Nurdin; Siska, Yulia (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
The problem in this research is that students' learning outcomes are not yet maximal. The purpose of this study was to determine the increase in social studies learning outcomes after following the scramble learning model for the fourth grade students of SDN 1 Penawar Jaya Tulang Bawang. This research uses Classroom Action Research (CAR). Data collection techniques using test questions, observation, and documentation. The results showed that the percentage of student activity in the first cycle of meeting 1 obtained a percentage of 57.14% (less) and at the second meeting a percentage of 67.86% (enough). In the second cycle at the first meeting the percentage was 82.14% (good) and at the second meeting the percentage was 92.86% (very good). While the aspect of learning outcomes at the pre-cycle stage obtained a percentage of 47.06%, increased in the first cycle to 64.71% and increased again to 88.24% in the second cycle. Based on the explanation above, it can be concluded that the application of the scramble learning model can improve social studies learning outcomes for fourth grade students at SDN 1 Penawar Jaya Tulang Bawang.